Pemberantasan Korupsi dan Sosok Birokrasi Masa Depan:Dilema Mewujudkan Tata Kepemerintahan yang baik dalam Kontak Pelayanan Publik - Miftah Toha (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2006)
Corruption has existed since the earliest man started living in an organization. In Indonesia, corruption now wxists in all levels of government institutions, both in central and regional ones, even it now already spreads among the society. The world sees that it becomes a worldwide basic need to eliminate corruptions forms. Reformation of bureaucracy towards good governance must be enforced bearing 3 leverage points, such as: 1) the leader, the president, the government institutions leaders and the leaders of all political parties, must be all together have willingbness to do reform of government institutions. 2) government institutions must be organized and managed effectively and afficiently. 3) efforts to build democratic and desentralistic government system are considered as the leverage factors of the reformation.